2008
DOI: 10.1159/000125550
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Deferasirox (Exjade®, ICL670) versus Deferoxamine in Sickle Cell Disease Patients with Transfusional Hemosiderosis

Abstract: Background/Aims: There is increasing evidence demonstrating the value of transfusions in sickle cell disease (SCD). However, resultant iron overload can be life threatening if untreated. Chelation therapy with deferoxamine requires parenteral infusions that can negatively impact quality of life and adherence to treatment. Methods: As part of a phase II trial, SCD patient-reported outcomes were evaluated. One hundred and ninety-five patients were randomized (2:1) to receive oral deferasirox (5–30 mg/kg/day) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 34 publications
3
43
0
1
Order By: Relevance
“…3,18 Patient satisfaction rates for deferasirox DT have been reported to be as high as 90%, 19 yet studies have shown that most patients dislike the mode of administration for deferasirox DT and would prefer to be able to take their medication with food. 20 Barriers such as these likely contribute to a reduced patient-reported adherence to deferasirox DT of 67-86%.…”
Section: Discussionmentioning
confidence: 99%
“…3,18 Patient satisfaction rates for deferasirox DT have been reported to be as high as 90%, 19 yet studies have shown that most patients dislike the mode of administration for deferasirox DT and would prefer to be able to take their medication with food. 20 Barriers such as these likely contribute to a reduced patient-reported adherence to deferasirox DT of 67-86%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances have led to the development of new oral iron chelators, such as deferasirox, which has changed the clinical practice in several transfusiondependent anemias with iron overload. Vichinsky et al suggest that treatment adherence with deferasirox may be better than that of desferrioxamine and thus it should lead to improved long-term outcomes [18]. Deferasirox mobilizes iron stores by binding selectively to the ferric form of iron.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous well-controlled clinical trials have demonstrated the efficacy of once-daily oral deferasirox in controlling liver iron concentration (LIC). [6][7][8][9][10][11] Deferasirox is preferred by patients, 12 improves compliance, 13 has a 12-to 16-hour half-life, 14,15 and is routinely prescribed 7 days per week. As a result, deferasirox chronically suppresses labile plasma iron levels better than intermittent, subcutaneous DFO therapy.…”
Section: Introductionmentioning
confidence: 99%